Recent trends in global advertising practice - Vardar, Nükhet (Henry Stewart Talks, 2009)
How globalization and global advertising are intertwined, Brief look at the history of globalization, The changing face of globalization, Importance of networking in globalization, The definition of global advertising, How global advertising has evolved, Advantages and disadvantages of global advertising, The future of global advertising, Value Paradox: culture and the global advertising link, Cultural deterritorialization and its effects on global advertising, Global advertising in the Middle East